Perspectives on Treatment of Inflammatory Bowel Disease in Older Patients: Applying Gut-Feeling in an Evidence-Based Era? - Vera E.R. Asscher; Cynthia M. Verbiest; Sanne N. Waars; Simon P. Mooijaart; Andrea E. van der Meulen-de Jong; Arwen H. Pieterse; P.W. Jeroen Maljaars (European Medical Journal)
Background: The older inflammatory bowel disease (IBD) population is challenging to treat because of heterogeneity in characteristics related to frailty. The authors aimed to study factors contributing to the difference in treatment between older and younger patients with IBD and the relation between frailty and therapy goals, from the perspectives of both professionals and patients with IBD. Methods: Semi-structured interviews in 15 IBD professionals and 15 IBD patients aged ≥65 years. Results: Professionals had 1–20 years of experience, and three practiced in an academic hospital. Patients were aged 67–94 years and had a disease duration between 2 years and 62 years. The authors found that professionals aimed more often for clinical remission and less often for endoscopic remission in older compared with younger patients. Older patients also aimed for clinical remission, but valued objective confirmation of remission as a reassurance. Professionals sometimes opted for surgery earlier in the treatment course, while older patients aimed to prevent surgery. Professionals’ opinion on corticosteroids in older patients differed, while patients preferred to avoid corticosteroids. In professionals and patients, there was a shift towards goals related to frailty in patients with frailty. However, professionals did not assess frailty systematically, but judged frailty status by applying a clinical view. Conclusions: Many therapy goals differed between older and younger patients, in both professionals and patients. Professionals did not assess frailty systematically, yet aspects of frailty influenced therapy goals. This underlines the need for clinically applicable evidence on frailty in IBD, which could aid tailored treatment.